Molecular identification of Cryptosporidium parvum from avian hosts - Quah, J. X.; Ambu, S.; Lim, Y. A. L.; Mahdy, M. A. K.; Mak, J. W. (Cambridge University Press, 2011)
Cryptosporidium species are protozoan parasites that infect humans and a wide variety of animals. This study was aimed at identifying Cryptosporidium species and genotypes isolated from avian hosts. A total of 90 samples from 37 different species of birds were collected throughout a 3-month period from April 2008 to June 2008 in the National Zoo of Kuala Lumpur, Malaysia. Prior to molecular characterization, all samples were screened for Cryptosporidium using a modified Ziehl-Neelsen staining technique. Subsequently samples were analysed with nested-PCR targeting the partial SSU rRNA gene. Amplicons were sequenced in both directions and used for phylogenetic analysis using Neighbour-Joining and Maximum Parsimony methods. Although 9 (10) samples were positive for Cryptosporidium via microscopy, 8 (8.9) produced amplicons using nested PCR. Phylogenetic trees identified all the isolates as Cryptosporidium parvum. Although C. parvum has not been reported to cause infection in birds, and the role of birds in this study was postulated mainly as mechanical transporters, these present findings highlight the significant public health risk posed by birds that harbour the zoonotic species of Cryptosporidium.